International market research project on filters (Philippines, Indonesia, Singapore and Thailand). - Wong, Victor Foo Keng. (2009)
This dissertation is focused on an international market research study of diesel filters. Lites Filter Inc is a Cummins wholly owned subsidiary. It designs, manufactures and distributes filters for use in high end diesel engine applications. Lites Filter has traditionally adopted a leveraged approach by tapping on Cummins' market share in the diesel engine market.